Effect of Perceived Health Benefits and Trust on Customer’s Satisfaction & Willingness to Pay for Organic Foods - Ghai, Sneha; Sharma, Ashok (Indian Journal of Community Health, 2019)
Background: Organic food has captured the market tremendously, yet the attitude and purchase intentions differ invariably. Many researchers have made an attempt to discuss the major barriers and motives to purchase and consume organic food. There is a need to identify how these factors contribute in drawing intention to but the organic food. Objectives: To assess the significance effect of perceived benefits & trust on willingness to pay premium prices for organic foods. Also, to test the effect of perceived benefits and trust on Customer’s satisfaction. Materials and Methods: Data on perceived benefit and trust derived from organic food was collected from 304 respondents from Delhi & NCR students hailing in different demographics through a convenience sampling technique. The authors have used structured, and pre-tested questionnaire. Linear Logistic regression analysis was done using SPSS 21.0 to find association between the perceived benefits and trust on consumer satisfaction and willingness to pay premium prices for organic food. Results: Trust and perceived benefits are the main predictors of WPPP for organic foods. Conclusion: The findings gave valuable insights for marketers to learn organic consumer’s profiles based on socio-economic variables & benefit perception. Other variables could also be used to different consumer segments with respect to their purchase behavior.